2015
DOI: 10.5005/jp-journals-10024-1647
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder in Facial Injuries: A Comparative Study

Abstract: Patients with disfiguring facial injuries had significantly higher PTSD levels compared to patients with nondisfiguring facial injuries, patients with orthopedic/visible injuries had statistically significant lower IES scores which could not be strictly termed PTSD when compared to patients with disfiguring facial injuries who had high scores of IES corresponding to high levels of PTSD and these results were observed at all three study intervals (DOD, 1 and 6 months postoperatively). Female patients with disfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Female gender was highly associated with anxiety and depression compared to male gender in patients below 50 years. However above 50 years gender was not a significant factor associated with either depression or anxiety [30]. This seems to concur with the findings where it was found that a larger percentage of females faced psychiatric morbidity compared to males.…”
Section: Socio-demographic and Clinical Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…Female gender was highly associated with anxiety and depression compared to male gender in patients below 50 years. However above 50 years gender was not a significant factor associated with either depression or anxiety [30]. This seems to concur with the findings where it was found that a larger percentage of females faced psychiatric morbidity compared to males.…”
Section: Socio-demographic and Clinical Characteristicssupporting
confidence: 89%
“…However, in contrast, Prashanth et al [30] did comparative studies on the severity of anxiety and depression among disfigured and non-disfigured facial injury patients. He found a significant difference between these two groups with disfigured having higher severity of the disorders.…”
Section: Socio-demographic and Clinical Characteristicsmentioning
confidence: 99%
“…Among these, the most common risk factor identified in the data set was female gender, with eight different studies reporting a positive correlation between female gender and a positive diagnosis of PTSD (5, 32, 37, 42, 53, 73, 75). Prashanth et al (37, 38), for example, reported that the mean score for IES was significantly higher in female patients with facial disfiguring injuries compared to male patients at all intervals. In a study specifically exploring gender differences in risk factors for PTSD among tsunami survivors, Pyari et al (53) concluded that women were 6.35 times more likely to have PTSD than men.…”
Section: Resultsmentioning
confidence: 99%
“…While nearly one fourth (24%) of the selected studies focused primarily on children and adolescents, there were significantly fewer studies (7%) whose primary focus were women—an equally vulnerable group. Countless studies exist—including those included in this review—that attest to the fact that women are at a significantly higher risk of PTSD, compared to men or the general population (32, 38, 42). A number of reasons suggest why women are at a higher risk of getting PTSD compared to men, including higher risk of exposure to specific types of traumatic events, average younger age at exposure, their social environment that generally provides fewer supportive resources, and stronger perceptions of threat and loss of control (86).…”
Section: Discussionmentioning
confidence: 99%
“…For Europe, the one-year estimate is 1.1% [ 10 ]. Acute psychiatric symptoms [ 11 ] and female sex [ 11 , 12 ] have been suggested to raise the probability of PTSD in trauma cases with disfiguring facial injuries [ 12 ]. It should be noted, however, that these studies often exclude patients with certain pre-existing psychiatric diagnoses and substance abuse, patient groups potentially with increased need for additional care resources.…”
Section: Introductionmentioning
confidence: 99%